Identitas Budaya Arab pada Rumah Masyarakat Arab Hadrami di Tanah Abang Jakarta (Studi Kasus Keluarga Al-Barqi) - Priyoyudanto, Febri; Abdullah, Amani (Universitas Al Azhar Indonesia, 2024)
The spatial design and application of ornaments in the houses of the Hadrami Arab community in Indonesia has its uniqueness. The distinctiveness features a combination or adaptation of cultures, resulting in a unique design character. This represents the cultural identity that is still maintained by the Hadrami Arab community in Tanah Abang, Central Jakarta. The type of research in this study is descriptive qualitative. The direct observation method is used to identify problems in the form of the application of space design and Arabic-style ornaments that are still maintained in the Hadrami Arab community house in Tanah Abang, Central Jakarta in the Hadrami Al-Barqi family. The findings of this research reveal the application of Arabic-style ornaments with Arabesque characteristics and also the application of space design with Arabic styles both classical and modern. This research is expected to contribute to public understanding of Hadrami Arab culture as a peranakan Arab community that also contributes to Indonesia's multicultural cultural repertoire.Keywords – Hadhrami Arabs, Cultural Identity, Spatial Design, Ornament.